2020
DOI: 10.1155/2020/6828043
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Loopamp Assay for the Diagnosis of Pulmonary Tuberculosis in Cambodia

Abstract: The Loopamp™ MTBC kit (TB-LAMP) is recommended by WHO for Mycobacterium tuberculosis complex detection in low-income countries with a still low drug-resistant tuberculosis (TB) rate. This study is aimed at testing its feasibility in Cambodia on sputa collected from presumptive tuberculosis patients. 499 samples were tested at a smear microscopy center and 200 at a central-level mycobacteriology laboratory. Using mycobacterial cultures as reference, TB-LAMP results were compared with those of LED fluorescent mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…Several miniaturized LAMP techniques, such as microfluidic, electrochemical, paperbased, and digital methods, have been developed for rapid sample processing and screening of pathogens [19]. One of the studies evaluated the efficiency of the WHO-approved TB-LAMP kit in a sputum sample of TB patients in LMIC and indicated its potential to be used at microscopy centers in a resource-limited setting [20]. Similarly, another study demonstrated the good sensitivity and specificity of TB-LAMP for Mtb detection in LMICs [21].…”
Section: Loop-mediated Isothermal Amplificationmentioning
confidence: 99%
“…Several miniaturized LAMP techniques, such as microfluidic, electrochemical, paperbased, and digital methods, have been developed for rapid sample processing and screening of pathogens [19]. One of the studies evaluated the efficiency of the WHO-approved TB-LAMP kit in a sputum sample of TB patients in LMIC and indicated its potential to be used at microscopy centers in a resource-limited setting [20]. Similarly, another study demonstrated the good sensitivity and specificity of TB-LAMP for Mtb detection in LMICs [21].…”
Section: Loop-mediated Isothermal Amplificationmentioning
confidence: 99%
“…The SSM method is time-saving but lacks sensitivity. 7,9 Due to the time-consuming nature or low sensitivity of the traditional methods, developing an early diagnosis strategy is challenging, making it easy for TB patients to miss the optimal treatment window. In recent decades, many molecular methods, including conventional PCR and PCR-based techniques (namely, multiplex PCR, GeneXpert, and real-time PCR assays), have been used for the detection of MTB in clinical applications.…”
mentioning
confidence: 99%
“…Mycobacterium culture, as a gold standard, is widely performed for the diagnosis of MTB. , Although mycobacterial culture is able to accurately identify MTB strains, the detection process is time-consuming (typically 4–8 weeks) and complicated (involving steps of isolation and identification), which cannot meet the demands of rapid detection. The SSM method is time-saving but lacks sensitivity. , …”
mentioning
confidence: 99%
See 1 more Smart Citation